PEDAGOGICAL CONDITIONS OF DEVELOPING STUDENTS' CREATIVE ABILITIES - Ismoilova N. S. (Bright Mind Publishing, 2025)
This article describes the pedagogical conditions that serve the development of students' creative abilities, the integration of innovative and traditional methods, and the effective use of didactic tools. The author scientifically analyzes the ways of developing students' independent thinking and creative approach by stimulating intellectual and creative activity. In the pedagogical process, important aspects of developing creative abilities are revealed through a combination of interactive methods, author's technologies, and modern technological tools.
Keywords: Creative abilities, innovative method, non-traditional approach, didactic conditions, creative potential, author's technology, pedagogical activity.